2008
DOI: 10.1159/000129687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Molecular Weight Fucoidan and Low Molecular Weight Heparin in a Rabbit Model of Arterial Thrombosis

Abstract: Background: Therapeutic use of unfractionated heparin and low molecular weight heparins (LMWHs) is limited by hemorrhagic adverse effects. We compared the antithrombotic effect of LMW fucoidan (LMWF) and LMWH in an experimental model. Methods: Thrombosis was induced in femoral arteries of male New Zealand White rabbits by in situ induction of endothelial apoptosis with staurosporine (10–5M for 30 min). Starting the day before apoptosis induction, the animals received subcutaneous LMWF (15 mg/kg), LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…1 and 6). Previously, fucoidan has been show to have antithrombotic effects (41)(42)(43). The reason for such opposite effects of fucoidan on platelets may be due to different molecular weights of fucoidan.…”
Section: Discussionmentioning
confidence: 99%
“…1 and 6). Previously, fucoidan has been show to have antithrombotic effects (41)(42)(43). The reason for such opposite effects of fucoidan on platelets may be due to different molecular weights of fucoidan.…”
Section: Discussionmentioning
confidence: 99%
“…High molecular weight fucans demonstrated a greater anticoagulant effect than structurally similar polysaccharides having lower molecular weight (Nishino & Nagumo 1991). Fucoidan has a stronger antithrombotic activity, but a lower anticoagulant activity and hemorrhagic risk than heparin (Durand et al 2008). The mechanisms of action are predominantly on HC-II mediated antithrombin activities, direct antithrombin action (thrombin-fibrinogen complex) and minor AT-III involvements (Shanmugam & Mody 2000).…”
Section: Thrombin and Factor Xamentioning
confidence: 99%
“…The presence of abundant 3-O-sulfated glucosamines in Heparan sulfates from human follicular fluid has suggested that some biological activities could be mimicked by other sulfated polysaccharides or derivatives (de Agostini et al, 2008). Low molecular weight fucoidan (LMWF) has been used to demonstrate this (Colliec et al, 1991, Millet et al, 1999and Durand et al, 2008.…”
Section: Commercial Products Patents and Applicationsmentioning
confidence: 99%